Resistência à fratura por lascamento de cerâmicas monolíticas - Taufer, Cristiano (2017)
This study estimated the chipping resistance (ReA) of two ceramics (GC-IPS e.max CAD and YZ- Zenostar Zr Translucent) using the edge chipping test, evaluating (1) if the edge distance (d) influences on the load to produce the chipping (F) and on ReA and (2) if the adhesion to a dentine analogue substrate (G10) influences on ReA. Bar-shaped specimens of 2 mm and 5mm in thickness were fabricated from GC and YZ. Specimens were adhesively cemented (C) to G10 or just fixed to the universal testing machine (NC). Chippings (n=25) were produced from preset d (0.1 mm – 0.6 mm) in all specimens (YZ-C; YZ-NC; GC-C and GC-NC) using a Vickers indenter connected to a universal testing machine with crosshead speed of 1 mm/min. F and d were recorded and ReA (F/d) was calculated. The data were statistically analyzed using Weibull distribution, Pearson correlation, Student t, ANOVA and Turkey (α =0.05). A strong positive correlation was found between F and d for all groups (R≥0.98). The ReAvalues showed a tendency to increased as the d increases, especially for NC ceramics. Such trend was confirmed for the C ceramics. ReAdepends on the material/condition evaluated.